Hydrous icaritin nanorods with excellent stability improves the in vitro and in vivo activity against breast cancer. (1st January 2020) - Wang, Yian; Huang, Tiantian; Li, Haowen; Fu, Jingxin; Ao, Hui; Lu, Likang; Han, Meihua; Guo, Yifei; Yue, Feng; Wang, Xiangtao
Abstract: Due to their various biological activities that are beneficial to human health and antitumor effect, flavonoid compounds have attracted much attention in recent years. Hydrous icaritin (HICT) was such a flavonoid that can inhibit the growth of breast cancer and cancer stem cells. In order to overcome the insolubility problem, HICT was fabricated into nanorods (NRs) through anti-solvent precipitation in this paper using D-α tocopherol acid polyethylene glycol succinate and sodium oleate as a co-stabilizer meanwhile using the mixture of ethanol and acetone (1:2, v/v) as the organic solvent. The obtained HICT NRs showed an average particle size 222.0 nm with a small polydispersity index value of 0.124 and a high zeta potential of – 49.5 mV. HICT NRs could maintain similar particle size in various physiological medium and could be directly lyophilized without the addition of any cytoprotectants and then reconstituted into a colloidal system of similar size. The resultant HICT NRs had a high drug loading content of 55.6% and released HICT in a steady and constant pattern. MTT assay indicated NRs enhanced HICT's antitumor activity to ninefold against MCF-7 breast carcinoma cells. In vivo studies demonstrated oral administration free HICT had almost no tumor inhibitory effect while HICT NRs showed a tumor inhibition rate of 47.8%. When intravenously injected, HICT NRs displayed similar therapeutic efficacy to paclitaxel injections (70.4% vs. 74.5%, TIR). This may be partly due to the high accumulation of the injected HICT NRs in tumor ranking only second to that in the liver but much higher than in other organs. These results demonstrated that HICT NRs could be a promising antitumor agent for the treatment of breast cancer in clinic.